2014
DOI: 10.1103/physrevlett.112.238303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Clustering and Chemotactic Collapse of Self-Phoretic Active Particles

Abstract: Recent experiments with self-phoretic particles at low concentrations show a pronounced dynamic clustering [I. Theurkauff et al., Phys. Rev. Lett. 108, 268303 (2012)]. We model this situation by taking into account the translational and rotational diffusiophoretic motion, which the active particles perform in their self-generated chemical field. Our Brownian dynamics simulations show pronounced dynamic clustering only when these two phoretic contributions give rise to competing attractive and repulsive interac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
249
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(258 citation statements)
references
References 49 publications
(88 reference statements)
9
249
0
Order By: Relevance
“…This agrees with recent experimental observations [5,6,16] and may shed light on the still mysterious mechanism underlying their appearance. (Competing explanations based on the chemoattractive KS instability either predict macrophase separation [26] or clusters shrinking with increasing v 0 [15].) Although we mainly report regular patterns in our figures, our model suggests that irregular cluster arrangements, more akin to patterns found in experiments with active colloids, can also be found depending on location in parameter space and boundary conditions (Videos 3-5, Supplemental Material [22]).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…This agrees with recent experimental observations [5,6,16] and may shed light on the still mysterious mechanism underlying their appearance. (Competing explanations based on the chemoattractive KS instability either predict macrophase separation [26] or clusters shrinking with increasing v 0 [15].) Although we mainly report regular patterns in our figures, our model suggests that irregular cluster arrangements, more akin to patterns found in experiments with active colloids, can also be found depending on location in parameter space and boundary conditions (Videos 3-5, Supplemental Material [22]).…”
mentioning
confidence: 67%
“…This mapping, which assumed that active colloids swim up chemical gradients (the "chemoattractive" case), can explain clustering, but leads to complete phase separation, rather than a self-limiting cluster size. A combination of a passive drift up the chemical gradient and self-propulsion down it ("chemorepulsion") might lead to finite size clusters [15]; however, at variance with experiments [5,16], these should shrink as the self-propulsion speed increases [15]. A more general study of chemoresponsive active colloids in the limit of fast chemical dynamics suggests a far larger potential for pattern formation than is predicted by the KS model [10].…”
mentioning
confidence: 95%
“…For example, if a motor tends to move toward high product concentrations, it will tend to move toward other motors that produce product leading to clustering in many‐motor systems. The collective dynamics of self‐diffusiophoretic motors present new features 55, 56, 57. Microscopic simulations of the collective behavior of Janus motors have shown that both chemical gradients and hydrodynamic effects are important in determining the nature of the observed inhomogeneous states 58.…”
Section: Resultsmentioning
confidence: 99%
“…Their emergent collective dynamics is a most fascinating topic. Interacting microswimmers may show turbulence at low Reynolds number [4] and exhibit dynamic clustering due to phoretic interactions [5][6][7] or motility-induced phase separation [8][9][10][11][12][13]. Their collective motion drives macroscopic fluid flow as in bioconvection [15] or vortex formation [16].…”
Section: Introductionmentioning
confidence: 99%